2021
DOI: 10.3390/toxins13120867
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Modification of the Anticancer Peptide LVTX-9 to Enhance Its Cytotoxicity against Malignant Melanoma Cells

Abstract: Spider venom is a valuable resource for the development of novel anticancer drugs. In this study, we focused on novel linear amphipathic α-helical anticancer peptide LVTX-9, which was derived from the cDNA library of the venom gland of the spider Lycosa vittata. The cytotoxicity of LVTX-9 against murine melanoma cells in the range of 1.56–200 μM was tested and found to be significantly lower than those of most anticancer peptides reported. Its IC50 was determined to be 59.2 ± 19.8 μM in a serum or 76.3 ± 12.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Another conclusion drawn in the same study showed the anti-proliferation property of LVTX-9-C18 from colonial formation testing [6]. There were three groups of variables: the control group, 10μM of LVTX-9 and 1μM of LVTX-9-C18.…”
Section: Enhanced Anticancer Effect Of Spider Peptide Lvtx-9 Through ...mentioning
confidence: 66%
See 4 more Smart Citations
“…Another conclusion drawn in the same study showed the anti-proliferation property of LVTX-9-C18 from colonial formation testing [6]. There were three groups of variables: the control group, 10μM of LVTX-9 and 1μM of LVTX-9-C18.…”
Section: Enhanced Anticancer Effect Of Spider Peptide Lvtx-9 Through ...mentioning
confidence: 66%
“…In a recent study done by Fengjiao Li et al, peptide LVTX-9 from Lycosa vittata was isolated to test its toxicity after modified by fatty acids (octadecanoic acid conjugation) [6]. The five lipopeptides produced had an increasing number of carbon atoms from 12 carbons to 20 carbons and an ascending order of hydrophobicity.…”
Section: Enhanced Anticancer Effect Of Spider Peptide Lvtx-9 Through ...mentioning
confidence: 99%
See 3 more Smart Citations